ROLE OF MODERN IMAGING TECHNIQUES IN ADDITIONAL VIZUALISATION OF BREAST CANCER: LITERATURE REVIEW - A. S. Ainakulova; D. R. Kaidarova; Zh. Zh. Zholdybai; N. I. Inozemtceva; M. O. Gabdullina; I. M. Karibayev (Сибирский онкологический журнал)
Background. Breast cancer is the most common cancer in women worldwide. Despite advances in treatment of breast cancer, early-stage breast cancer detection is limited by screening mammography and often requires additional breast imaging.The purpose of the study was to analyze available data on modern imaging techniques of additional breast visualization used for improving breast cancer screening.Material and methods. The review includes data from randomized controlled trials and meta-analyzes on the effectiveness of breast imaging techniques for early-stage breast cancer detection. The search was carried out in pubmed, Web of science, scopus and cochrane library databases. Out of 100 publications published over the past 7 years, 51 were included in the presented review.Results. Breast cancer screening using various imaging techniques has been carried out in the world for more than 30 years, and over the past 10 years significant progress has been made in improving X-ray, ultrasound and magnetic resonance technologies in the early breast cancer detection. At present, healthcare organizers are faced with the question of choosing a vector for improving the breast cancer screening program by introducing digital tomosynthesis, contrast spectral mammography, or accelerated mri. According to the current results of the analysis of literature data, contrast spectral mammography and accelerated mri have the highest sensitivity, but studies of sensitivity, specificity, positive and negative predictive values (ppv, npv) are ongoing.Conclusion. The data presented in the review confirm the necessity for finding the vector for improving the breast cancer screening program using multicenter prospective trials.